Diarrheagenic Escherichia coli pathotypes investigation revealed atypical enteropathogenic E. coli as putative emerging diarrheal agents in children living in Botucatu, São Paulo State, Brazil - Dias, Regiane C. B. [UNESP]; dos Santos, Bruna C. [UNESP]; dos Santos, Luis F.; Vieira, Melissa A. [UNESP]; Yamatogi, Ricardo S. [UNESP]; Mondelli, Alessandro L. [UNESP]; Sadatsune, Terue [UNESP]; Sforcin, José M. [UNESP]; Gomes, Tânia A. T.; Hernandes, Rodrigo T. [UNESP] (Wiley, 2016)
The aim of the present study was to investigate the prevalence of Diarrheagenic Escherichia coli (DEC) pathotypes, a leading cause of diarrhea worldwide, among diarrheal and healthy children, up to 5 years of age, living in the city of Botucatu, São Paulo, Brazil. DEC, investigated by PCR detection of virulence factor-encoding genes associated with the distinct pathotypes, was isolated from 18.0% of the patients, and 19.0% of the controls, with enteroaggregative E. coli (EAEC), the most frequent pathotype, being detected in equal proportion between patients and controls (10.0%). Among the enteropathogenic E. coli (EPEC) isolates, only one isolate was able to produce the localized adherence pattern to HeLa cells, being thus the only typical EPEC identified. All the remaining EPEC were classified as atypical (aEPEC), and detected in 8.0% and 8.5% of the patients and controls, respectively. Regarding the serotypes, 26.5% of the analyzed EPEC isolates belonged to classical EPEC-serogroups, and the only two STEC found were serotyped as O26:H11 (patient) and O119:H7 (control). Antimicrobial susceptibility tests revealed that 43.6%, 29.5% and 2.6% of the DEC isolates were resistant to ampicillin, cotrimoxazole and gentamicin, respectively. Our data indicate that EAEC remains prevalent among children living in Botucatu, and revealed atypical EPEC as emerging putative diarrheal agents in this geographical region.
Keywords: Adherence; Antimicrobial resistance; Diarrheagenic Escherichia coli; Enteropathogenic E. coli; Intimin serotype